EFFECT OF PROGRESSIVE MUSCLE RELAXATION ON SLEEP QUALITY AMONG PATIENTS WITH CHRONIC DISEASES: A LITERATURE REVIEW - Syafa'atun Mirzanah; Sri Yona; Debie Dahlia (Belitung Nursing Journal, 2020)
Background: Sleep disturbance is prevalent among patients with chronic diseases. Thus, the use of non-pharmacological interventions is needed. Progressive muscle relaxation is considered effective to improve sleep quality, but its discussion is still limited. Objective: To investigate the effect of progressive muscle relaxation on sleep quality among chronic disease patients. Design: Literature review. Data Sources: Search was performed through the CINAHL, Science Direct, and ProQuest database from 2014 to 2019 for English-based, full-text research articles. Review Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methods was used to select articles. Critical Appraisal Skills Programme was used for quality assessment. Results: From the 644 articles yielded, six articles were included. Progressive muscle relaxation could be given alone or in combination with cognitive behavioural therapy. It also has been proven to improve sleep quality among patients with chronic diseases regardless their ages. Procedures in progressive muscle relaxation vary, but all studies reported significant improvements on sleep quality. Most of studies used audio as a medium for progressive muscle relaxation training. Conclusion: Progressive muscle relaxation significantly improves the sleep quality among patients with chronic diseases. It is recommended for future studies to compare the effectivity between 4 or 7 muscle groups and 16 muscle groups on sleep quality.